The Influence of Earnings Management on Pharmaceutical Company Stock Prices - Stefanie Valencia Kezia Kalengkian; Sheren Laura Lasaru; I Gusti Agung Musa Budidarma (Jurnal Ekonomi dan Bisnis Digital, 2023)
This research was conducted to determine and analyze the effect of earnings management on the stock prices of pharmaceutical companies in Indonesia. In this study, earnings management is the independent variable and stock prices are the dependent variable. The sample used is a pharmaceutical company listed on the Indonesia Stock Exchange. The sampling method was carried out using purposive sampling. Detection of earnings management behavior in this study was measured using the modified Jones model. The data analysis technique uses the classical assumption test, namely the multicollinearity test and the heteroscedasticity test by testing the hypothesis using multiple linear regression. The results of this study indicate that pharmaceutical companies actually practice earnings management by reducing profits as seen from the average negative discretionary accruals (DA). According to the results of the study, earnings management has no effect on the stock prices of pharmaceutical companies listed on the IDX. This means that there are other factors that will further influence the movement of pharmaceutical company stock prices in Indonesia in 2017-2021.